The tensile strength analysis of kenaf fibre reinforced epoxy composites by using Weibull distribution / Abdul Hakim Abdullah and Razali Hassan - Abdullah, Abdul Hakim; Hassan, Razali (2014)
This paper presents the tensile strength analysis of unidirectional kenaf fibre reinforced epoxy composites that statistically analyzedby using two parameters Weibull distribution. The specimens were made from hand lay-up techniques and compressed in a mould for fabrication process. Pure epoxy specimen and two fibre volume fractions ratios of 15% and 45% were fabricated and subjected to tensile load up to failure. The two parameterWeibull distribution has confirmed that the increasing of fiber volume fraction in composites showed an improvement in tensile strength and lowering dispersion of fracture strength, as well described by the scanning electron microscope evaluation.The confidence level and reliability of kenaf/epoxy composites is presented in a graph form in which the probability material will failed was obtained. For safe utilization in design and manufacturing, this method is likely more appropriate instead of taken as a single mean tensile strength. It is found that the high reliability values of tensile strength of 15% and 45% kenaf reinforced epoxy composites are 30 MPa and 60 MPa respectively.